INFLUENCE OF CARBON EMISSION DISCLOSURE ON FIRM VALUE OF INDUSTRIAL FIRMS IN INDONESIA - Aspian Noor; Yoremia Lestari Ginting (International Journal of Contemporary Accounting, 2022)
The purpose of this research is to analyze the effect of carbon emission disclosure, environmental performance and environmental cost on Firm Value. This research uses 40 firms as sample from 50 industrial sector firms listed on Indonesian Stock Exchange in 2019-2020 as population. Samples are determined by purposive sampling. This research uses secondary data derived from annual reports, sustainability reports, financial reports, and stock price data. Data analysis method used in this research is Multiple Linear Regression using SPSS 26 Software. The first finding in this study showed that carbon emission disclosure had a significant and positive effect on firm value, this implies that the more detailed information on carbon emissions that is disclosed, the higher the firm's value, and vice versa. The second findings of this study showed that environmental performance has no significant effect on firm value, this indicates that environmental performance has no impact on the value of a firm, this demonstrates that investors continue to disregard environmental performance as measured by the ISO 14001 environmental standard when making investment decisions. The last findings of this study showed that environmental cost had an insignificant effect on firm value because investors still do not consider environmental costs when making investment decisions and because many industrial sector firms have not disclosed environmental costs in their social responsibility reports, so investors continue to miss the signals given by firms. This research contributes to the development of the sustainability accounting field.